Organoleptic Test of Instant "Beras Kencur" with Various Kinds of Sugar as Sweeteners - Herawati, Jajuk; Thohiron, Mochamad; Indarwati, Indarwati; Gusti, Anggi Septian Eridho (Journal of Applied Plant Technology, 2024)
The study aimed to determine the level of preference of the panelists in the instant organoleptic test of kencur rice with various kinds of sugar as sweeteners. The research was carried out in June – July 2023 at the Production Laboratory of the Faculty of Agriculture, Wijaya Kusuma Surabaya. The one-factor Complete Random Design Research Method (RAL) consists of 3 treatments of sugar sources (G) as sweeteners, namely G1 = sugar sweetener; G2 = brown sugar sweetener; G3 = palm sugar sweetener. The observation parameters were through a hedonic test on the properties of the product, namely taste, aroma, texture, color, and physical appearance, as well as determining the level of preference of the panelists for kencur rice instant drink from 3 types of sugar as sweeteners.  Each treatment was repeated three times with 10 panelists per repetition. This Hedonic test with sensory analysis of kencur rice instant products is used to estimate what products are most liked by the panelists with the level of preference. The method used in the Hedonic Test with sensory analysis, consists of 5 levels: (1) very disliked, (2) disliked, (3) mediocre, (4) liked, and (5) strongly liked. The results of the research show that the type of sugar has an effect on the acceptance of the sweetness level of the panelists. Organoleptic test on product properties: palm sugar has an advantage in aroma, brown sugar has an advantage in texture, then granulated sugar has an advantage in color and physical appearance.